Draft Genome Sequence of Thermoanaerobacter sp. Strain A7A, Reconstructed from a Metagenome Obtained from a High-Temperature Hydrocarbon Reservoir in the Bass Strait, Australia - Li, Dongmei (American Society for Microbiology, 2013)
The draft genome sequence of Thermoanaerobacter sp. strain A7A was reconstructed from a metagenome of a microbial consortium obtained from the Tuna oil field in the Gippsland Basin, Australia. The organism is a strict anaerobe that is predicted to ferment a range of simple sugars and undertake sulfur reduction.